The energy sensor AMPK orchestrates metabolic and translational adaptation in expanding T helper cells - Mayer, Katharina A; Smole, Ursula; Zhu, Ci; Derdak, Sophia; Minervina, Anastasia A; Salnikova, Maria; Witzeneder, Nadine; Christamentl, Anna; Boucheron, Nicole; Waidhofer-Söllner, Petra; Trauner, Michael; Hoermann, Gregor; et al. (FASEB journal, 2021)
The importance of cellular metabolic adaptation in inducing robust T cell responses is well established. However, the mechanism by which T cells link information regarding nutrient supply to clonal expansion and effector function is still enigmatic. Herein, we report that the metabolic sensor adenosine monophosphate-activated protein kinase (AMPK) is a critical link between cellular energy demand and translational activity and, thus, orchestrates optimal expansion of T cells in vivo. AMPK deficiency did not affect T cell fate decision, activation, or T effector cell generation; however, the magnitude of T cell responses in murine in vivo models of T cell activation was markedly reduced. This impairment was global, as all T helper cell subsets were similarly sensitive to loss of AMPK which resulted in reduced T cell accumulation in peripheral organs and reduced disease severity in pathophysiologically as diverse models as T cell transfer colitis and allergic airway inflammation. T cell receptor repertoire analysis confirmed similar clonotype frequencies in different lymphoid organs, thereby supporting the concept of a quantitative impairment in clonal expansion rather than a skewed qualitative immune response. In line with these findings, in-depth metabolic analysis revealed a decrease in T cell oxidative metabolism, and gene set enrichment analysis indicated a major reduction in ribosomal biogenesis and mRNA translation in AMPK-deficient T cells. We, thus, provide evidence that through its interference with these delicate processes, AMPK orchestrates the quantitative, but not the qualitative, manifestation of primary T cell responses in vivo.
Keywords: fyziologická adaptace; regulace genové exprese enzymů; myši; Gene Expression Regulation, Enzymologic; T-Lymphocytes, Helper-Inducer; Adoptive Transfer; kolitida; buňky Th17; Animals; Lymphocyte Activation; převzatá imunita; adenylátkinasa; CD4-pozitivní T-lymfocyty; Mice; regulační T-lymfocyty; AMPK; T cell; cellular metabolism; DNA vazebné proteiny; aktivace lymfocytů; Adenylate Kinase; CD4-Positive T-Lymphocytes; RNA, Messenger; DNA-Binding Proteins; zvířata; Colitis; myši knockoutované; T-lymfocyty pomocné-indukující; messenger RNA; Th1 buňky; T-Lymphocytes, Regulatory; Th1 Cells; translation; Mice, Knockout; Th17 Cells; Adaptation, Physiological